SCHOOL STRATEGIES IN HANDLING DEVIANT BEHAVIOR AND LOW STUDENT LEARNING MOTIVATION. CASE STUDY AT STATE SENIOR HIGH SCHOOL 1 SUWAWA - Abdan, Hasna; Ahmad, Nurlaila; Utina, Ramli; Maryati, Frida (International Journal of Cultural and Social Science, 2025)
This study focuses on analyzing deviant behavior and low learning motivation in students at SMA Negeri 1 Suwawa, and how teacher competency and school strategies influence these dynamics in the context of implementing the Independent Curriculum and character education. Using a descriptive qualitative approach with a case study design, this study involved 30 students selected through purposive sampling, as well as teachers and education personnel as supporting informants. Data were collected through in-depth interviews, observation, and documentation, then analyzed using qualitative analysis techniques and assisted by NVivo 14 software for theme coding. The results indicate that deviant behavior and low learning motivation are closely related to teacher competency in implementing values-based learning, authentic assessment, and differentiated learning. Furthermore, the study revealed a significant gap between teachers' actual abilities and the demands of the Independent Curriculum, necessitating reinforcement through needs-based Teacher Professional Development (TPD) planning. These findings provide important implications: schools need to build a systematic character education ecosystem supported by ongoing teacher professional development to more effectively transform student behavior and learning motivation.